Construction of triblock copolyesters via one-step switchable terpolymerization of epoxides, phthalic anhydride and ε-caprolactone using dual urea/organic base catalysts. Issue 6 (13th January 2022) - Lin, Limiao; Chen, Xin; Xiang, Huanxin; Chang, Min; Xu, Yonghang; Zhao, Hongting; Meng, Yuezhong
Abstract : A cost-effective and efficient system of ureas/organic bases toward the controlled self-switchable copolymerization of epoxide/PA/CL to obtain well-defined triblock polyesters. Abstract : In this study, triblock copolyesters were synthesized via a switchable terpolymerization of mixed monomers of epoxides, phthalic anhydride (PA) and ε-caprolactone (CL) by using cost-effective dual urea/organic base catalysts. Different combinations of urea/organic base pairs were evaluated in order to optimize the catalytic activity and switchable selectivity, and different types of epoxides were employed to obtain diverse copolyesters. The sequence structures of the obtained copolyesters were analyzed by gel permeation chromatography (GPC) and diffusion-ordered NMR spectroscopy (DOSY) measurements. The switchable mechanism of the ROP of lactones and ROAC of epoxide/anhydride cycles was investigated via in situ analysis of 1 H NMR, GPC and ATR-IR spectroscopy. The results showed that the N, N ′-dicyclohexylurea (U1)/bis(triphenylphosphine)iminium chloride (PPNCl) pair with more alkaline urea exhibited the highest catalytic activity for the mixture of cyclohexene oxide, PA and CL in both ring-opening alternating copolymerization (ROAC) and ring-opening polymerization (ROP) reaction cycles as compared to those previously reported. It was found that the existence/exhaustion of PA could be considered to be the switch between ROAC and ROP reaction cycles, and that the superior catalytic selectivity contributed to the successful formation of the desired triblock sequence structures.